The Physical Mechanisms Behind the Change in the Precipitation Recycling Rate in the Mid- and Lower Reaches of the Yangtze River - Guo, Wen-Kang; Wang, Xi-Yu; Gao, Wang-Ze; Yong, Jia-Hua; Bao, Xin-Yue; Wu, Yong-Ping; Feng, Guo-Lin; Dong, Wen-Jie (Frontiers in Physics, 2021)
Precipitation recycling rate (PRR) is an important index to understand the physical mechanism behind the effect of different water vapor on regional precipitation. In this paper, based on the evaluation model of PRR, the change in PRR in the middle and lower reaches of the Yangtze River (MLRYR), the correlation between PRR and external water vapor and local evaporation, and the possible reasons of the interannual variation of PRR were studied, using Chinese stations precipitation data and NCEP/NCAR reanalysis data. The results show that the mean PRR in the MLRYR for 1961-2017 was the largest in autumn (about 0.3) and the smallest in summer (about 0.23), with an obvious upward trend (passed the 95% significance F-test) except that in summer and the highest trend coefficient of PRR in autumn (0.38), indicating that the contribution of external water vapor to local precipitation was reduced. The PRR of the MLRYR are highly related to the water vapor input through the western boundary and the southern boundary, and the water vapor is mainly from the northwest Pacific Ocean, the South China Sea and the Bay of Bengal. And the upward trend of PRR is probably because the SST of the Pacific was not conducive to the development of the northwest Pacific anticyclone, which restrained the water vapor input into MLRYR from the Western Pacific, South China Sea and Bay of Bengal. We suggest that SST rise in Pacific Ocean, South China Sea, especially in Indian Ocean will have an important impact on precipitation in East Asia, which should be paid more attention.